Prohibition of lutah darah marriage according to 'urf: A case study on the community of Deling Village, Sekar District, Bojonegoro Regency - Fauziyah, Ririn; Shidiq, Agus Sholahudin (Asy-Syari’ah : Jurnal Hukum Islam, 2025)
The prohibition of lutah darah marriage is a cultural practice preserved by the Deling Village community in Sekar District, Bojonegoro Regency, which forbids marriage involving routes that pass through the father's birthplace. This research explores the relevance of this prohibition in the context of Islamic law and its classification as al-'urf al-sahih or al-'urf al-fasid. The study aims to analyze the legitimacy of this custom as a legal basis in Islamic jurisprudence and its implications for social harmony. A qualitative descriptive method was employed, involving interviews with local traditional leaders, observations of community practices, and analysis of secondary sources. The findings indicate that the lutah darah prohibition meets the criteria of al-'urf al-sahih, as it aligns with Islamic legal principles, does not contradict the nass, and has been practiced consistently to prevent perceived familial and social disharmony. This study concludes that the custom reflects a form of localized Islamic jurisprudence that accommodates societal traditions while upholding the objectives of maqasid al-shari'ah.